STRATEGI PEMERINTAH DALAM PENERAPAN SISTEM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 KECAMTAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Fatima Fatima; Muhammad Ikbal; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
Government's Strategy in Implementing Online Learning Systems during the Covid-19 Pandemic in Pitu Riawa District, Sidenreng Rappang Regency. (Supervised by Mr. Muhammad Ikbal and Mrs. Erfina).The purpose of this study is to determine the government's strategy in implementing an online learning system during the Covid-19 pandemic in Pitu Riase District, Sidenreng Rappang Regency and also to find out what factors influence government satregi in implementing an online learning system during the Covid-19 pandemic in the District Pitu Riase, Sidenreng Rappang Regency.The study population was 2230 parents / guardians / guardians of students from 26 schools. While the research sample was 96 people. While the sampling used is quota sampling, using quantitative descriptive research, and the data collection techingues used in this study are by using techinque 1). Observation, 2). Questionnaire, 3). Interview, 4) Literature study. The collected data were then analyzed using a frequwncy tabel and using tehe SPSS 21 application.The resluts of this study indicate that the Government's Strategy in Implementing Online Learning Systems during the Covid-19 Pandemic in Pitu Riawa district, Sidenreng Rappang regency can be categorized as good with a percentage of 62.8%. The factors that affect the online learning system strategy during the Covid-19 pandemic are a). The information system factor has an impact of 0.6%, b). The learning process ability factor has an impact of 2%, c). Allocation factors for means of impact are 7.2 and 10.4% d). The standard organizational structure has an impact of 1.5%, e). The policy factor regarding HR management has an impact of 6.2%.